EFEK PENGGUNAAN DANA KIP-K DALAM PEMENUHAN KEBUTUHAN PENDIDIKAN DI LINGKUNGAN MAHASISWA - Abelia Patrisia Hemuto; Frahmawati Bumulo; Abdul Rahim Maruwae; Radia Hafid; Rierid Koniyo (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Financial constraints are often the main obstacle for low-income students in fulfilling their higher education needs. This quantitative survey-based study aims to analyze the effect of using Kartu Indonesia Pintar Kuliah (KIP-K) funds on meeting the educational needs of students in the Economic Education Department, Class of 2022, Faculty of Economics and Business, Gorontalo State University. The study sample includes 50 KIP-K recipient students selected using a purposive sampling technique. Data were collected via structured Likert-scale questionnaires and analyzed using simple linear regression, t-tests, and coefficient of determination. The test results revealed that the use of KIP-K funds had a positive and significant effect on meeting educational needs, with a regression equation Y ˆ=17.056+0.852X, t_